2018
DOI: 10.1364/ol.43.000462
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic and electric hotspots via fractal clusters of hollow silicon nanoparticles

Abstract: We show that fractal clusters of hollow Si nanoparticles provide both magnetic hotspots (MHs) and electric hotspots (EHs). The hollow size tailors the wavelength dependence of the field enhancement. In the wavelength window 400-750 nm, magnetic field intensity enhancements of 10-3790 and electric field intensity enhancements of 10-400 are achievable. Wavelength-tuned MHs and EHs allow better enhancement of Raman optical activity, fluorescence and circular dichroism of molecules, and so on. Si nanoparticles ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Strong local magnetic fields can be used to control or detect small quantum objects (quantum dots, atoms, and molecules) supporting magnetic optical transitions. [ 50 ] Magnetic hot‐spots are also useful for spectroscopy, [ 51 ] better enhancement of Raman scattering, fluorescence, and circular dichroism of molecules, [ 52 ] sensing, [ 53 ] and other applications.…”
Section: Resultsmentioning
confidence: 99%
“…Strong local magnetic fields can be used to control or detect small quantum objects (quantum dots, atoms, and molecules) supporting magnetic optical transitions. [ 50 ] Magnetic hot‐spots are also useful for spectroscopy, [ 51 ] better enhancement of Raman scattering, fluorescence, and circular dichroism of molecules, [ 52 ] sensing, [ 53 ] and other applications.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, it is shown that fractal clusters of hollow silicon nanoparticles provide both electric and magnetic hotspots. In the wavelength window 400–750 nm, electric field intensity enhancements of 10–400 and magnetic field intensity enhancements of 10–3790 are reported 35 .…”
Section: Introductionmentioning
confidence: 97%
“…Electric and magnetic hotspots provided by dimers and trimers of solid 28,29 and hollow nanoparticles 30 may find application in single molecule experiments. Hotspots provided by disordered and fractal aggregates of nanoparticles are also studied 3135 . In particular, it is shown that fractal clusters of hollow silicon nanoparticles provide both electric and magnetic hotspots.…”
Section: Introductionmentioning
confidence: 99%